2019
DOI: 10.3390/met9101029
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Selectively Laser Melted CoCrFeMnNi High Entropy Alloy

Abstract: CoCrFeMnNi high entropy alloys (HEAs) were additively manufactured (AM) by laser powder bed fusion and their corrosion resistance in 3.5 wt% NaCl solution was studied by potentiodynamic polarization and electrochemical impedance spectroscopy tests. A systematic study of AM CoCrFeMnNi HEAs’ porosity under a wide range of laser processing parameters was conducted and a processing map was constructed to identify the optimal laser processing window for CoCrFeMnNi HEAs. The near fully dense AM CoCrFeMnNi HEAs exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Compared with the conventionally cast HEAs, the CoCrFeNiMn fabricated using LAAM possessed significantly higher yield strength and ultimate tensile strength, because of the finer grains. Ren et al [ 13 ] and Xu et al [ 14 ] comparatively analyzed the corrosion behavior of the SLM-produced and as-cast CoCrFeMnNi HEA in 3.5 wt % NaCl solution. Compared with as cast material, CoCrFeMnNi high-entropy alloy prepared by SLM had better composition uniformity and better corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventionally cast HEAs, the CoCrFeNiMn fabricated using LAAM possessed significantly higher yield strength and ultimate tensile strength, because of the finer grains. Ren et al [ 13 ] and Xu et al [ 14 ] comparatively analyzed the corrosion behavior of the SLM-produced and as-cast CoCrFeMnNi HEA in 3.5 wt % NaCl solution. Compared with as cast material, CoCrFeMnNi high-entropy alloy prepared by SLM had better composition uniformity and better corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [383] reported the superior corrosion resistance of SLM-built CoCrFeMnNi HEA compared to its arc-melted counterpart because of the homogeneous elemental distribution and lower density of micro-pores in SLM sample acting as local anodic sites and inhibiting the nucleation and growth of new pits. In a similar study, the corrosion behavior of CoCrFeMnNi HEA manufactured using SLM in 3.5 wt.% NaCl solution was studied by Xu et al [361].…”
Section: Laser-processed Heasmentioning
confidence: 99%
“…A. Ayyagari, Hasannaeimi, Grewal, et al, 2018;Ren et al, 2019;Todai et al, 2017). HEAs are composed of multiple principal elements that result in unique strengthening mechanisms and resistance to failure under dynamic loading.…”
Section: Mechanochemical Degradationmentioning
confidence: 99%
“…Therefore, it is paramount to investigate and understand the electrochemical response during mechanochemical degradation in vivo under dynamic loading. In terms of design and development of new metallic biomaterials, a new generation of biocompatible alloys named high‐entropy alloys (HEAs) and bulk metallic glasses (BMG) show excellent mechanical and corrosion behaviour that is superior in many cases compared to presently used bioimplant materials (A. Ayyagari, Hasannaeimi, Arora, Hasannaeimi, Arora, & Mukherjee, 2018; A. Ayyagari, Hasannaeimi, Grewal, et al., 2018; Ren et al., 2019; Todai et al., 2017). HEAs are composed of multiple principal elements that result in unique strengthening mechanisms and resistance to failure under dynamic loading.…”
Section: Electrochemical Measurements Sensors and Degradation Mechanmentioning
confidence: 99%